Technology’s Dual Role in Challenging and Supporting OSH and VDC Professionals - Rudolf, Emilie Marie; Kjærgaard, Asta; Zielinski Nguyen Ajslev, Jeppe (Nordic Journal of Working Life Studies, 2026)
In this study, we examine how occupational safety and health (OSH) professionals and virtual design and construction (VDC) professionals navigate the use of technology for OSH purposes and how the interdisciplinarity between the two professions affects their occupational identities. Through a positioning analysis of interviews with OSH and VDC professionals, we conclude that the use of technology both challenges and supports the identity of OSH professionals. Technology enhances collaborative and alliance building aspects of OSH professionals’ identity; however, it is in risk of replacing dialogue, a core aspect of OSH professionals’ work. We find that cooperation between the two groups may enhance VDC professionals’ identity, as it allows them to exude collaborative competencies. Interdisciplinarity is a fruitful path for enhancing the use of technologies for OSH purposes, but the conservative nature of the construction industry poses a challenge to this.